2018
DOI: 10.21873/anticanres.12489
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Multiparametric MRI in 800 Men Submitted to Repeat Prostate Biopsy: Results of a Public Health Model

Abstract: mpMRI used as a triage test could reduce the need for prostate biopsies by about 45%, thereby improving cost-effectiveness, however, patients should be informed of the false-negative rate associated with mpMRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
0
9
0
1
Order By: Relevance
“…The test measures the amount of two genes that are associated with aggressive prostate cancer with a high NPV for Grade Group ≥2 (Gleason score ≥7). In definitive, SelectMDx combined with mpMRI could better select men candidates to AS ruling out patients who do not have csPCa improving the cost-effectiveness (25)(26)(27). In a multicenter study including 916 men submitted to initial prostate biopsy, Haese et al (28) reported a sensitivity, specificity and NPV of SelectMDx in the diagnosis of csPCa equal to 93, 47 and 95%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The test measures the amount of two genes that are associated with aggressive prostate cancer with a high NPV for Grade Group ≥2 (Gleason score ≥7). In definitive, SelectMDx combined with mpMRI could better select men candidates to AS ruling out patients who do not have csPCa improving the cost-effectiveness (25)(26)(27). In a multicenter study including 916 men submitted to initial prostate biopsy, Haese et al (28) reported a sensitivity, specificity and NPV of SelectMDx in the diagnosis of csPCa equal to 93, 47 and 95%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the PI-RADS score at high risk for csPCa irrespective of clinical findings many parameters have been reported: index lesion diameter, shape and location of the lesion (25) and the ADC values (4,7,9). Wu et al (9) showed that higher ADC values (0.830×10 -3 mm 2 /sec) were significantly associated with low-risk prostate cancer; on the contrary, Kim et al (6) reported a mean ADC value for csPCa equal to (0.741±0.164) ×10 -3 mm 2 /sec.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of TPBx in the diagnosis of csPCa (Gleason score>6 and/or greatest percentage of cancer for single core>50%) was evaluated (13); moreover, the Clavien-Dindo grading system for the classification of biopsy complications was used (14). Finally, the diameter of mpMRI lesion, the presence of PI-RADS score 3 vs. 4 and ADC values were evaluated in men with csPCa; in this respect, a receiver operating characteristic (ROC) curve was calculated in the peripheral mpMRI lesions to evaluate the diagnostic performance of ADC values as well as to determine the ADC cut-off level that provided the highest diagnostic performance. For statistical analysis the Student's t-test was used; a p-value <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…The most influential economic study on UK prostate biopsy policy is the Faria et al [9] model, drawing on the PROMIS study [10], on which UK guidelines are largely based. Other economic studies support the use of mpMRI first line [33][34][35][36] and newer biomarker tests appear cost effective compared with a first-line biopsy [37,38]. However, comparison with mpMRI first line is unknown.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%